Evaluation of Indirect Enzyme-Linked Immunosorbent Assays and IgG Avidity Assays Using a Protein A-Peroxidase Conjugate for Serological Distinction between Brucella abortus S19-Vaccinated and -Infected Cows - Pajuaba, Ana C. A. M. (American Society for Microbiology (ASM), 2010)
This study aimed to evaluate the use of protein A-peroxidase (horseradish peroxidase [HRPO]) in indirect enzyme-linked immunosorbent assays (iELISAs) and IgG avidity assays for serological distinction between Brucella abortus S19-vaccinated and -infected cows. Four groups were analyzed: GI, 41 nonvaccinated seropositive cows; GII, 79 S19-vaccinated heifers analyzed at 3 months postvaccination; GIII, 105 S19-vaccinated cows analyzed after 24 months of age; and GIV, 278 nonvaccinated seronegative cows. IgG levels and avidity to B. abortus smooth lipopolysaccharide (S-LPS) were determined using anti-bovine IgG-HRPO or protein A-HRPO conjugates. Similar levels of IgG anti-S-LPS were found with GI using both conjugates. Lower IgG levels were detected with GII, GIII, and GIV using protein A-HRPO. Both conjugates showed high performance in discriminating GI from GIII, with high sensitivity (Se; 97.6%) and specificity (Sp; 97.1%). Protein A-HRPO was better in distinguishing GI from GIV (Se, 97.6%; Sp, 94.6%) and GI from GII (Se, 80.5%; Sp, 94.9%). Protein A-HRPO excluded a higher number of positive samples with GII and GIV. IgG avidity showed that protein A-HRPO, but not anti-IgG-HRPO, was able to distinguish nonvaccinated from vaccinated cattle, showing a higher avidity index (AI) with GI than with GII, with 78% of serum samples in GII showing an AI of <50%. Therefore, the iELISA using B. abortus S-LPS antigen and protein A-HRPO conjugate for preferential detection of the IgG2 subclass was shown to be suitable for serological distinction between S19-vaccinated and -infected cows. Also, antibodies generated after vaccination showed lower avidity, suggesting a role for the IgG2 subclass as an antibody of higher-affinity maturation after infection, constituting an additional tool for differentiating vaccinated from infected cattle.